The Frequency of Phantom Vibration Syndrome in Medical Staff: A Cross Sectional Survey - Usman Riaz, Shafqat Perveen, Muniba Afzal, Idrees Ahmed Zahoor, Iqra, Romasa Sarwar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Phantom vibration syndrome, also known as hypovibochondria or ring-xiety, may occur among individuals carrying digital devices. Phantom vibration syndrome is the mistaken belief that a device is vibrating when it is not. The current study investigates this phenomenon among medical staff who often interact with digital devices throughout duty hours. Objective: The objective of the study was to determine the frequency of Phantom vibration syndrome in medical staff. Methods: A cross-sectional survey of medical staff was conducted. A convenience sample of 150 physicians, surgeons, allied health professionals, and medical assistants was used. Online survey invitations were sent by email, WhatsApp, and other channels. The data was analysed by SPSS 25.0. The Fisher exact test was used to compare phantom vibrations to categorical data. Results: The results showed that out of 190 medical staff, there were 133 (72.7%) having phantom vibration syndrome. It was significantly associated (p=0.000) with younger age groups from 21-40 year, was seen more in surgeon, physicians and then nurses (p=0.029), associated more with carrying cell phone (p=0.003), more in carrying device in breast and back pocket (p=0.001), more in keeping device on vibration always or most of time (p=0.008) and more in using device from 11-15 or more hours (p=0.001). It was equally distributed in both male females (p=0.176) Conclusion: The study concluded that phantom vibration syndrome was highly prevalent in medical staff. The findings were associated with the length of time the product was used and were more prevalent among surgeons, medical physicians, and nurses in a decreasing order. most respondents regarded the feelings as bothersome and worth stopping and even changing the device. Keywords: Phantom Vibration Syndrome, Medical Staff, Health Practitioner, Digital Devices